PENGARUH GAYA KEPEMIMPINAN SITUASIONAL, KOMPENSASI, LINGKUNGAN KERJA TERHADAP MOTIVASI SERTA KEPUASAN KARYAWAN PADA DINAS PENDAPATAN DAERAH KABUPATEN LUMAJANG - Yuliansyah, Anton (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstrak: Research titled Influence Situational leadership style, Compensation, Environmental Working towards Motivation and Job Satisfaction on the Market Office of Jember Regency aims to analyze and determine the effect of Situational Leadership styles, Compensation, Environmental Working towards Motivation and Job Satisfaction on Market Agency. The population in this study were all employees at the Department of Revenue Lumajang. The research sample of 50 respondents, the method of accidental sampling. To know and analyze the influence of leadership style Situational, Compensation, Environmental Working towards motivation and job satisfaction of employees at the Market Office Jember while the method of analysis in this study were Path Analysis (Path Analysis) and the results of this study are variable leadership style Situational (X1) , Compensation (X2) and the Working Environment (X3) was significantly to variable Motivation (Z) and variable leadership style Situational (X1), compensation (X2) and the Working Environment (X3) was significantly to variable job satisfaction (Y), and Motivation ( Z) significant effect on job satisfaction (Y). With the research is expected to provide additional insight into the benefits of the development of science and consideration, contribute ideas or useful information for the Department of Revenue Lumajang for decision making. Keywords: style situational leadership, compensation, work environment, motivation and job satisfaction